Integration of quanitative trait locus (QTL) for Tuber Colour variations with Genomic information in Sweet Potato - Reshma T.K (Department of Plant Biotechnology, College of Agriculture, 2019)
The study entitled Integration of Quantitative Trait Loci (QTL) for tuber colour variations with genomic information in sweet potato (Ipomoea batatas L.) was conducted at section of extension and social sciences, ICAR-CTCRI. The main objective of the study was to identify the differentially expressed genes for various tuber colours in sweet potato using RNA sequenced data; to integrate QTL information on tuber colour with genomic information in sweet potato and to validate the identified candidate genes. Sweet potatoes are abundant in compounds of biological effects such as β-carotene, phenolic acids and anthocyanins which gives its unique flesh colours. Here, a comparative transcriptomic analysis was performed to reveal the differentially expressed genes in six sweet potato cultivars with varying flesh colours of white, orange and purple. A total of 22,534, 27,431, 22,590 differentially expressed genes were identified in the pairwise analysis of orange and white, orange and purple and purple and white libraries respectively. Among differentially expressed genes, 5472 were upregulated and 17,062 were downregulated in orange compared to white, 11,670 upregulated genes and 15,761 downregulated genes in orange compared to purple, 7,622 were upregulated and 14,968 were downregulated in purple compared to white. Functional annotation of transcripts associated with the carotenoid biosynthesis pathway revealed the genes involved in the carotenoid biosynthesis pathway. In the present study, alignment of flanking SSR markers sequences of the QTL controlling β-carotene trait was done with the sweet potato genome assembly showed the position of QTL region on the chromosome. Functional annotation of the identified chromosomal region resulted in the identification of five candidate genes for carotenoid biosynthesis from three QTLs for β-carotene. Transcriptome sequencing and fine mapping of QTL are the efficient ways for discovering novel genes involved in main pathways. The identification of agronomically important genes can be utilized for improvement of sweet potato by the introduction of the genes to commercial sweet potato cultivars and for marker assisted selection.